2015
DOI: 10.1093/molehr/gav060
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic inheritance of cryptorchidism susceptibility in the LE/orl rat

Abstract: This work was supported by: R01HD060769 from the Eunice Kennedy Shriver National Institute for Child Health and Human Development (NICHD), 2P20GM103446 and P20GM103464 from the National Institute of General Medical Sciences (NIGMS), and Nemours Biomedical Research. The authors have no competing interests to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…23 We observed strong nuclear expression of PAX7 and/or myogenin in scattered mesenchymal cells between muscle layers. EdU labeling showed that proliferation is robust in the myogenic zone, and many EdU+ cells also express PAX7, as shown previously in studies of striated muscle myogenesis.…”
Section: Discussionmentioning
confidence: 69%
“…23 We observed strong nuclear expression of PAX7 and/or myogenin in scattered mesenchymal cells between muscle layers. EdU labeling showed that proliferation is robust in the myogenic zone, and many EdU+ cells also express PAX7, as shown previously in studies of striated muscle myogenesis.…”
Section: Discussionmentioning
confidence: 69%
“…Two possible mechanisms may underlie the association between exposure to specific PBDEs and cryptorchidism: a ) competition at the androgen receptor level, to block the effects of endogenous androgens (e.g., in the gubernaculum muscle or inguinoscrotal fat pad) ( Barthold et al 2016 ; Kaftanovskaya et al 2012 ) and/or b ) effects on the Leydig cell in the fetal testes, resulting in endogenous androgen insufficiency ( Houk et al 2004 ; Wang et al 2009 ). Stoker et al ( Stoker et al 2005 ) reported that BDE-99 and -100 display antagonistic properties in the rat ventral prostate binding assay ( of 33 and , respectively), while BDE-154 has a weak effect; they also found that BDE-100 is a true competitor at the androgen receptor level ( ) and inhibits dihydrotestosterone-induced androgen receptor activation in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20% of NS patients have HCM (Nishikawa et al ., ), of these 95% have a RAF1 mutation which results in increased kinase activity (Pandit et al ., ; Razzaque et al ., ). On the other hand, breeding studies in cryptorchid rat strains have shown an altered expression of genes that participate in muscle development, and in the contraction of tissues that participate in testicular descent (Barthold et al ., ). There is evidence which indicate that the Ras/MAPK pathway participates in muscle cell differentiation both with negative (Yang et al ., ; Yokoyama et al ., ) and positive effects (Li & Johnson, ; Cho et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that some of the 57 patients without any CNV detected in this study harbor RIT1 CNVs. On the other hand, recent evidence from breeding studies of a cryptorchid rat strain (Barthold et al ., ); and from association studies in both pigs (Elansary et al ., ) and man (Barthold et al ., ) have suggested that cryptorchidism is inherited as a polygenic trait, whit different variants contributing to susceptibility. Therefore, we suggest that the RAF1 microduplication detected in this study represents one of these variants.…”
Section: Discussionmentioning
confidence: 99%